Efeito dos tratamentos de superfície no manchamento e na rugosidade do esmalte após clareamento dentário - Debora Drummond Hauss Monteiro (2015)
Dental enamel bleached with peroxide can have increased roughness and susceptibility to staining, specially right after bleaching treatment, when compared to the enamel that has never been bleached. This studys goal was to evaluate the effect of different surface treatments and waiting period recommended for contact with dyes, on enamel roughness and susceptibility to staining after tooth bleaching. A hundred bovine specimens were bleached with 35% hydrogen peroxide (Whiteness HP, FGM) and treated according to five groups: G1 artificial saliva, G2 2% sodium fluoride (Flugel, DFL), G3 casein phosphopeptide-amorphous calcium phosphate fluoride paste (CPP-ACPF, MI Paste Plus, GC), G4 rinse for maintenance of colorachieved with bleaching (Keep White Rinse, DMC), G5 coronary polishing with aluminum oxide impregnated disks (Super Buff Disk, Shofu). Fifty specimens were immersed in coffee for 24 hours immediately after surface treatment, and the other fifty one hour after. Color difference (E) and roughness (Ra m, Rq) were evaluated by spectrophotometry (Vita EasyShade) before bleaching (L1), after bleaching (L2) and after staining (L3). Roughness was evaluated by profilometry (NewView 7300,Zygo Corporation) before bleaching (R1), after bleaching (R2) and after surface treatments (R3). Surface treatments and waiting period effects were analyzed with 2 way ANOVA, Friedman and Kruskal-Wallis (p<0,05). According to ANOVA, surface treatments (p=0,878), the waiting period of one hour (p=0,105) and the interaction (p=0,145) werent relevant to maintain the color achieved with dental bleaching. There was a significant difference on roughness between the evaluation moments (R1, R2 e R3) (p<0,001), but there was no statistical difference between surface treatments (G1, G2, G3, G4, G5) (p>0,05). Surface treatments were similar to control regarding staining prevention of bleached enamel. The waiting period of one hour for contact with dye wasnt relevant for maintenance of bleached enamel color. Enamel roughness was higher after bleaching. Surface treatments were similar to artificial saliva and significant on roughness reduction of bleached enamel.